Management of Development Funds And The Phenomena of Suburbanization - Analysis of Selected Polish Cases - Lukasz KONOPIELKO; Jacek SIERAK (Communications of International Proceedings, 2021)
This article concerns the challenges related to the management of public funds in the context of suburbanization phenomena. Theories of economic development and their implications for the directions of state intervention are presented. Based on the example of spending European funds in Poland, the rationale for this intervention is discussed. Systematic research concerns the surroundings of two urban centers in Poland - Wrocław and Kielce. Examples of projects and conclusions from direct surveys conducted among stakeholders are analyzed. Although any suburbanization processes are important for the analyzed regions, they are not adequately included in development programs implemented with the support of the EU funds.
Keywords: Suburbanization; EU Funds; Development.